MUNASABAH AYAT DALAM SURAH AL-QALAM PERSPEKTIF SEMITIC RHETORICAL ANALYSIS (SRA) - Sujiat Zubaidi; Dini Amalia Fattah; Aqdi Rofiq Asnawi (LP2M Universitas PTIQ Jakarta, 2023)
Criticism of the Quran has been a part of Quranic studies for some time. One of the figures who criticized the Quran is Richard Bell, an orientalist, who, in his book titled